MOTIVASI BERBELANJA PAKAIAN ONLINE MAHASISWA JURUSAN KOMUNIKASI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU PEKANBARU - ", Martalena; Razif, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Online clothes shopping is a way of shopping by using current technology internet. Progress media changed the way the fulfillment of one's needs will compliance clothing.Trand including online clothing shop is in great demand all people. Motivation is an impulse or desire for someone to do something you want to achieve the objectives of certain research, shopping for clothes online is that students 2012. Student generation communication communications online shopping for clothes because of the needs, lifestyle, influence of friends and the influence of advertising. Clothing is a primary need or basic human needs to be filled.Clothing is one tool to protect body. The purpose of this study was to determine whether the motivation that drives students to buy clothes online and how characteristics of students mentioned. As for researchers used theoretical basis is motivation, lifestyle and consumption. Whereas this study using Quantitative Descriptive, using purposive sampling technique or aims. Collection sample data by observation / direct observation, questionnaires, guided interviews and documentation. The number of respondents in this study as many as 24 people. Based on the results of the research, respondents choose online shopping for clothes because the clothes offered a nice, unique, cheap and not spending complex.Keywords: Motivation, Online Clothes Shopping